Three new species in the genus Chanohirata (Hemiptera: Cicadellidae: Deltocephalinae: Penthimiini) from China - Wang, Dongming; Zhang, Yalin (Zootaxa, 2022)
Two morphologically similar genera of Penthimiini, Chanohirata Hayashi & Machida, 1996 and Reticuluma Cheng & Li, 2005 are reviewed. Three new species, Chanohirata yunnana, C. minima and C. plania spp. nov., are described and illustrated and a new synonymy is proposed: C. theae (Matsumura, 1912) equals Reticuluma testacea (Kuoh, 1991) syn. nov. The following new combinations are also proposed for species previously included in Reticuluma: C. bipennata (Xu, Yu, Dai & Yang) comb. nov., C. dactyla (Fu & Zhang) comb. nov., C. eurya (Fu & Zhang) comb. nov., C. hamata (Wang & Zhang) comb. nov., C. lini (Cheng & Li) comb. nov., C. lageniformia (Wang & Zhang) comb. nov. and C. spinata (Cheng & Li) comb. nov. As a result, the definition of Reticuluma is restricted to include only the type species, R. citrina Cheng & Li, which differs from Chanohirata in having an apical process on the male pygofer. A species checklist and a key to all known species of Chanohirata are presented along with a distribution map for China.